2017
DOI: 10.1111/jocd.12315
|View full text |Cite
|
Sign up to set email alerts
|

Dermal morphological changes following salicylic acid peeling and microdermabrasion

Abstract: Both methods stimulate the repair process. The mechanisms underlying these variations are open for further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Rajan & Grimes also demonstrated an insignificant sebum level reduction on the forehead after a single Al 2 O 3 microdermabrasion procedure. A histological study by Abdel‐Motaleb et al found that the sebaceous glands to be large and surrounded by numerous inflammatory cells after microdermabrasion treatment. Tan et al observed a dramatic decrease of sebum content after 5 sessions of Al 2 O 3 microdermabrasion, which was not maintained between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Rajan & Grimes also demonstrated an insignificant sebum level reduction on the forehead after a single Al 2 O 3 microdermabrasion procedure. A histological study by Abdel‐Motaleb et al found that the sebaceous glands to be large and surrounded by numerous inflammatory cells after microdermabrasion treatment. Tan et al observed a dramatic decrease of sebum content after 5 sessions of Al 2 O 3 microdermabrasion, which was not maintained between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Microdermabrasion, moderate to deep chemical peels, fractional radiofrequency microneedling, and fractional non-ablative and fractional ablative lasers, all demonstrate an induced wound repair response on histology [137][138][139] . Recent molecular analysis suggests that fractionated ablative CO 2 laser accomplishes this through alteration of inflammatory signal pathways, with damage-activating innate immune responses that in turn trigger the activation of retinoic acid-dependent pathways [140] .…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…D'autres constituants majeurs de la matrice extracellulaire du derme, comme les protéoglycanes et les GAG, impactés par le vieillissement, peuvent être ciblés par des traitements anti-âge : c'est le cas, notamment, du C-xyloside qui stimule la production et le dépôt de ces composants, notamment de GAG [31], ainsi que des collagènes de la jonction dermo-épidermique [32]. Au niveau de l'épiderme, l'application d'exfoliants chimiques, comme l'acide trichloroacétique (TCA) ou des alpha/bêta-hydroxyacides (AHA ou BHA), permet de supprimer des couches cellulaires épidermiques, à des profondeurs variables selon les molécules utilisées, ce qui active la prolifération cellulaire et peut contribuer à restaurer l'architecture du tissu [33]. de cellules de Langerhans.…”
Section: Conséquences Des Défauts Vasculaires Cutanés Chez La Personnunclassified